FACTORS AFFECTING THE ABUNDANCE OF RUDERAL SPECIES AND Megathyrsus maximus, AN INVASIVE C4 GRASS IN ATLANTIC FOREST RESTORATION SITES - Dias, Jézili; Torezan, José Marcelo Domingues (Floresta, 2020)
The non-native grass Megathyrsus maximus (Guinea grass) have been reported as a threat for woody species regeneration in the first years of tropical forest restoration, in some cases persisting for several years. The objective of this work was to evaluate forest restoration sites, correlating M. maximus and other ruderal species density and dry biomass with reforestation age, canopy openness, species richness, abundance of planted trees, and soil fertility. Seventeen sites reforested with native species were selected, with planting ages between 40 and 110 months, at the Capivara Reservoir, Southern Brazil. In each site, ten 10-m2 plots each with four 1-m2 subplots were installed, where soil fertility, plant abundance (M. maximus, native and ruderal species) and dry biomass (M. maximus and ruderal species only) were recorded. All sites showed high fertility soils, and the canopy openness (21.5 a 38.5 %) decreased with time. Ruderal species abundance were positively correlated with canopy openness and negatively correlated with planting age. Both dry biomass (ranging from 0 to 182 g/m²) and clump density (ranging from 0 to 2 clumps per m²) of M. maximus were not correlated with reforestation age or canopy cover. Moreover, with the exception of soil magnesium concentration, none of soil fertility variables could explain M. maximus abundance or biomass, indicating a high phenotypic plasticity in this non-native grass species. It was remarkable that almost 10 years after planting, the reforested sites did not successfully suppress Megathyrsus maximus even though canopy openness decreased.